1986
DOI: 10.2307/3586546
|View full text |Cite
|
Sign up to set email alerts
|

"Information Gap" Tasks: Do They Facilitate Second Language Acquisition?

Abstract: This article reports the findings of the latest of a series of studies conducted to determine the effects of task type and participation pattern on language classroom interaction. The results of this study are compared to those of an earlier investigation (Pica & Doughty, 1985a) in regard to optional and required information exchange tasks across teacher‐directed, small‐group, and dyad interactional patterns. The evidence suggests that a task with a requirement for information exchange is crucial to the genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
250
2
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 331 publications
(268 citation statements)
references
References 12 publications
12
250
2
4
Order By: Relevance
“…These are similar to the T-units and c-units used in previous NfM research, Gass and Varonis 1985;Doughty and Pica 1986;Rulon and McCreary 1986;Pica et al 1989) but with a much more detailed definition that allows 'messy' spoken data to be coded in a principled way. They divide the spoken word into syntactically complete units and can be used to calculate how frequently certain features occur in numbers of speech samples.…”
Section: Data Collection and Codingmentioning
confidence: 86%
See 1 more Smart Citation
“…These are similar to the T-units and c-units used in previous NfM research, Gass and Varonis 1985;Doughty and Pica 1986;Rulon and McCreary 1986;Pica et al 1989) but with a much more detailed definition that allows 'messy' spoken data to be coded in a principled way. They divide the spoken word into syntactically complete units and can be used to calculate how frequently certain features occur in numbers of speech samples.…”
Section: Data Collection and Codingmentioning
confidence: 86%
“…Varonis and Gass 1985;Gass and Varonis 1985;Doughty and Pica 1986;Rulon and McCreary 1986;Pica et al 1989; see also Pica 1994 for an overview). Such studies suggested that information gap tasks transacted by dyads were likely to give most opportunities for NfM.…”
Section: The Role Of the Negotiation For Meaning In Slamentioning
confidence: 99%
“…The criteria I estabhshed for both tasks used inthis t study was based in part on priorresearch in second language acquisition (Doughty & Pica, 1986;Pellettieri, 2000;Pica, Kanagy & Falodun, 1993;.Pica, Lincoln-Porter, Paninos & Linnell, 1996) which looked at characteristics oftasks that induced interaction or best facilitated the negotiation of meaning. Being unable to find such tasks that also required students to make full use ofthe resources available ina CALL classroom forced me to create original network-oriented tasks.…”
Section: Task Designmentioning
confidence: 99%
“…Whether face-to-face or CALL-based, prior studies which make use of communicative tasks (Doughty and Pica, 1986;Gass and Varonis, 1985;Long 1983;Pellietieri, 2000;Pica et al, 1989;Pica et al,1996;Plough and Gass, 1993) have not taken advantage of the resources provided by a networked classroom. Typical jigsaw or info-gap tasks often take the form ofdescribing pictures to determine differences or reorganizing objects on a pasteboard to resemble a picture.…”
Section: Task Designmentioning
confidence: 99%
“…The way that learners manage their conversation to express their meaning at informational level has influential influence on their interlanguage as they use their language potential in turn, discussion, and discourse management [9]. Whether instruction in its incidental or intentional sense has any role in pushing learners to have extended and complex utterances is still open to research.…”
Section: Introductionmentioning
confidence: 99%